Human management and hybridization shape treegourd fruits in the Brazilian Amazon Basin. (4th May 2017) - Ambrósio Moreira, Priscila; Mariac, Cédric; Zekraoui, Leila; Couderc, Marie; Rodrigues, Doriane Picanço; Clement, Charles R.; Vigouroux, Yves
Abstract: Local people's perceptions of cultivated and wild agrobiodiversity, as well as their management of hybridization are still understudied in Amazonia. Here we analyze domesticated treegourd ( Crescentia cujete ), whose versatile fruits have technological, symbolic, and medicinal uses. A wild relative ( C. amazonica ) of the cultivated species grows spontaneously in Amazonian flooded forests. We demonstrated, using whole chloroplast sequences and nuclear microsatellites, that the two species are strongly differentiated. Nonetheless, they hybridize readily throughout Amazonia and the proportions of admixture correlate with fruit size variation of cultivated trees. New morphotypes arise from hybridization, which are recognized by people and named as local varieties. Small hybrid fruits are used to make the important symbolic rattle ( maracá ), suggesting that management of hybrid trees is an ancient human practice in Amazonia. Effective conservation of Amazonian agrobiodiversity needs to incorporate this interaction between wild and cultivated populations that is managed by smallholder families. Beyond treegourd, our study clearly shows that hybridization plays an important role in tree crop phenotypic diversification and that the integration of molecular analyses and farmers' perceptions of diversity help disentangle crop domestication history.